"... Порвалася нескінчена розмова". Про дослідницькі зацікавлення Стефанії Андрусів - Качмарчик, М. (Слово і Час, 2019)
Стаття презентує оглядовий портрет професорки Стефанії Андрусів, головні акценти її наукової й викладацької роботи. Описано люблінський період творчості української дослідниці. Учена брала активну участь у розвитку та популяризації україністичних студій у Польщі, а також у польсько-українському діалозі й співпраці. У своїй науковій діяльності, особливо люблінського періоду, професорка С. Андрусів використовувала найсучасніші дослідження й методології: постмодерністський інструментарій, теорію інтертекстуальності, наратологію, антропологію, а також активно застосовувала методи постколоніальної критики. The paper presents a scholarly profile of professor Stefaniia Andrusiv, paying specific attention to her achievements in the fields of research and education during her work at the John Paul II Catholic University of Lublin. In 2001 professor Andrusiv started her work at the Institute of Slavic Philology and in the academic year 2005/2006 became the head of the newly founded Department of Ukrainian literature holding this post until 2013. The scholar took an active part in popularizing Ukrainian studies in Poland and was very concerned about developing Polish-Ukrainian dialogue. In the course of her fruitful work at the university professor Andrusiv met different research and educational challenges and proposed many valuable initiatives. She effectively used contemporary research trends, such as postmodern methodology, the theory of intertextuality, the literary theory of narratology, as well as anthropology and postcolonial criticism. As far as her didactic work is concerned, professor Andrusiv delivered very interesting, thoughtprovoking lectures on the history of Ukrainian literature. Her professional approach was much appreciated not only by her students but by academic staff as well. The lectures on cultural studies, master’s and doctoral seminars belong to her didactic achievements and constitute a valuable heritage of education. It should be underlined that under the supervision of professor Andrusiv twelve students have successfully defended their Ph.D. dissertations and the majority of them continue their scholarly work. Professor Andrusiv never was afraid of making experiments, finding new solutions and approaches. Her mind was very flexible, creative and free of any obstructive restraints.